Predictability of Entrepreneurship Studies and Environmental Conditioning on Attitude Towards Entrepreneurial Intention Among University Students - Enyelunekpo R. Roberts; Francis O. Obisesan; Nada T. Uranta; Emmanuel E. Uye (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah, 2026)
This study investigates how entrepreneurship studies and environmental conditioning predict attitudes toward entrepreneurial intention among university students in Rivers State, addressing rising unemployment. Using a cross-sectional survey and purposive sampling, data from 230 students across four tertiary institutions were collected via questionnaires and analyzed using multiple regression. The results show that entrepreneurship studies and environmental conditioning jointly (R² = .477, p < .001) and independently (entrepreneurship studies: β = .438, p < .001; environmental conditioning: β = .401, p < .001) significantly predicted attitudes toward entrepreneurial intention. Conclusively, both factors are excellent predictors of entrepreneurial attitudes. Therefore, the study recommends that universities and government agencies make entrepreneurship education more practical and engaging to encourage graduates toward self-employment.